2015
DOI: 10.1001/jamapediatrics.2014.3351
|View full text |Cite|
|
Sign up to set email alerts
|

Survival and Morbidity of Preterm Children Born at 22 Through 34 Weeks’ Gestation in France in 2011

Abstract: The substantial improvement in survival in France for newborns born at 25 through 31 weeks' gestation was accompanied by an important reduction in severe morbidity, but survival remained rare before 25 weeks. Although improvement in survival at extremely low gestational age may be possible, its effect on long-term outcomes requires further studies. The long-term results of the EPIPAGE-2 study will be informative in this regard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
439
2
22

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 638 publications
(492 citation statements)
references
References 28 publications
29
439
2
22
Order By: Relevance
“…We found that frequencies of prematurity (21%) and SGA (24%) were high in patients with NS compared with the general population in France (7 and 5% respectively) (18). Patients with NS were significantly shorter at birth compared with healthy neonates, but had normal birth weight and head circumference, indicating an asymetrical SGA.…”
Section: Discussionmentioning
confidence: 73%
“…We found that frequencies of prematurity (21%) and SGA (24%) were high in patients with NS compared with the general population in France (7 and 5% respectively) (18). Patients with NS were significantly shorter at birth compared with healthy neonates, but had normal birth weight and head circumference, indicating an asymetrical SGA.…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, SGA, AGA, LGA, and Z score for BW all report measures standardized for GA and sex, and as such are often used as surrogate markers for fetal growth. Increased mortality in LBW infants with CHD does not address the question of whether fetal growth—as measured by SGA/AGA/LGA or Z score for BW—impacts this outcome since the increased mortality rate in LBW infants is mainly driven by lower GA, and it is well known that GA is a major determinant of mortality in infants with7, 8, 25 and without CHD 26…”
Section: Discussionmentioning
confidence: 99%
“…Paediatric follow-up visits with these children are in place to manage and diagnose or eventually treat some complications, especially neurological impairments. Other studies have shown that the majority of new-borns who make it through the early neonatal critical period will survive without major lesions or defects or with only moderate difficulties [15,19,20].…”
Section: Limitations Of the Studymentioning
confidence: 99%